Formation of the matrix-isolated difluoromethylselanes XCF2SeH (X = H, Cl) through photolysis of selenoacetic acids, XCF2C(O)SeH - Gomez Castaño, Jovanny Arles (2013)
Two hitherto unknown difluoromethylselanes, HCF2SeH and ClCF2SeH, were formed by photolysis of difluoroselenoacetic and chlorodifluoroselenoacetic acids isolated in solid argon. The progress of the photolysis was monitored by FTIR spectroscopy. The photoproducts were identified by comparison of experimental with theoretically predicted spectra and reported spectra for known species. The photochemical decomposition mechanisms of HCF2C(O)SeH and ClCF2C(O)SeH is presented. Matrix photochemistry has been successfully employed for the formation of two hitherto unknown selane molecules, HCF2SeH and ClCF2SeH, by starting from HCF2C(O)SeH and ClCF2C(O)SeH acids. The species were identified through their IR spectra, with the assistance of ab initio and DFT methods.